Age-Stratified Phase I Trial of a Combination of Bortezomib, Gemcitabine, and Liposomal Doxorubicin in Patients with Advanced Malignancies - Falchook, G. S. (2011)
BACKGROUND: Preclinical data suggest synergistic activity of bortezomib, gemcitabine, and liposomal doxorubicin. Because tolerance to therapy may be attenuated in elderly patients, we performed an age-stratified phase I trial of this combination. PATIENTS AND METHODS: Two parallel age-stratified arms (<65 and ≥65 years old) were accrued (3+3 design). Starting doses included bortezomib 0.7 mg/m(2) (days 1 and 8), gemcitabine 500 mg/m(2) (days 1 and 8) and liposomal doxorubicin 20 mg/m(2) (day 1). RESULTS: In the <65-year old group, 65 patients were treated; the maximum tolerated dose was bortezomib 1.3 mg/m(2), gemcitabine 800 mg/m(2), and liposomal doxorubicin 35 mg/m(2). In the ≥65-year old group, 28 patients were treated; the recommended phase II dose was bortezomib 1.0 mg/m(2), gemcitabine 800 mg/m(2), and liposomal doxorubicin 20 mg/m(2). Dose-limiting toxicities included thrombocytopenia and neutropenia. The most common toxicities were mild cytopenias, fatigue, and neuropathy. Ten patients achieved partial responses (6 of 7 patients with cutaneous T-cell lymphoma; 4 of 16 patients with small cell carcinomas, including lung, prostate, ovarian, and nasopharyngeal). CONCLUSION: Combination bortezomib, gemcitabine and liposomal doxorubicin is well-tolerated, but with a lower recommended phase II dose in elderly patients, and demonstrated antitumor activity, especially in T-cell and small cell histology malignancies.